Analysis of MHD stability and active mode control on KSTAR for high confinement, disruption-free plasma. (10th April 2020) - Park, Y.S.; Sabbagh, S.A.; Ahn, J.H.; Park, B.H.; Kim, H.S.; Berkery, J.W.; Bialek, J.M.; Jiang, Y.; Bak, J.G.; Glasser, A.H.; Kang, J.S.; Lee, J.; et al.
Abstract: Long-pulse plasma operation at high normalized beta, βN, above the n = 1 ideal MHD no-wall stability limit in KSTAR is presently limited by tearing instabilities rather than resistive wall modes. H-mode plasma operation during the recent KSTAR device campaign produced discharges having strong m / n = 2/1 tearing instabilities at βN lower than the ideal MHD no-wall beta limit. The unstable tearing mode consequently reduced plasma confinement and toroidal plasma rotation significantly. The experiment confirmed that an extended duration of electron cyclotron heating (ECH) at the initial phase of the discharge plays a critical role in mode destabilization. To study destabilizing mechanisms that affect the mode growth, the stability of the observed tearing modes from plasmas with significantly different βN is computed by using the resistive DCON code and the M3D-C 1 code employing different physics. The computed tearing stability index, Δ′, differs between the mode that is destabilized by the early ECH at lower βN, and the mode that is destabilized at higher βN with observed mode triggering activity. Equilibrium reconstructions that include constraints from internal profile diagnostics are used as input for reliable computation of stability. The modified Rutherford equation (MRE) describing the evolution of the neoclassical tearing mode (NTM) island width has been constructed for KSTAR plasmas by using plasma parameters computed by the TRANSP code. In preparation for long-pulse plasma operation at higher beta utilizing increased plasma heating power, a resistive wall mode (RWM) active feedback control algorithm that includes magnetic sensor compensation of the prompt applied field and the field from the induced current on the passive conductors has been completed and enabled on KSTAR. Use of multiple toroidal sensor arrays is enabled for increased control performance by including the effect of varied mode helicities in the outboard region where the mode measurement is made. This analysis on beta-limiting instabilities and active mode control provides the required foundation for high confinement plasma operation on KSTAR without disruption.